Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India - Mirza, Zeeshan A. (Zootaxa, 2017)
Scorpions of the genus Liocheles Sundevall, 1833 are widespread in forests of the Indo-Pacific region; however, its species diversity is poorly resolved. A new species of the genus Liocheles is herein described from northeast India after examination of freshly collected specimens and available museum material. The new species, Liocheles schalleri sp. nov., occurs in the Indo-Burma biodiversity hotspot, a region that has been poorly explored for its arachnid diversity.